EVALUATION OF HEAVY METALS IN TWO MAJOR INGREDIENTS OF AMPUCARE (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
The World Health Organization (WHO) estimates that 4 billion people or 80 percent of the world population, presently use herbal medicine for some aspect of primary health care and 25% of modern medicines are made from plants first used traditionally. There are several reports of adverse effects of these herbal preparations due to the presence of high level of heavy metals such as Lead, cadmium, chromium, nickel, arsenic and mercury and this problem has become a matter of concern. The present study was done to check the presence of lead, cadmium, chromium, nickel, arsenic and mercury in two major ingredients (Azadirachta indica and Curcuma longa) of a polyherbal product- Ampucare. These ingredients were procured from different cities of India and subjected to analysis by Atomic Absorption Spectrophotometer (AAS). Results were compared with the permissible limits (PL), acceptable daily intake (ADI) and provisional maximum tolerable daily intake (PMTDI) as set by World Health Organization (WHO), Food and Drug Administration (FDA) and Joint FAO/WHO expert committee on food additives (JECFA). All the metals were within these limits. Mean levels were evaluated with respect to their place of procurement. Delhi samples had highest mean metal contamination followed by Lucknow, Chandigarh and Chennai samples. Lowest metal contamination was found in Srinagar samples. These results were also in correlation with the safe limits as well as pollution prevailing in these cities. Overall study confirmed the safety of Ampucare.